Atypical clinical features associated with mixed pathology in a case of non-fluent variant primary progressive aphasia. Issue 1 (4th March 2019) - De Leon, Jessica; Mandelli, Maria Luisa; Nolan, Amber; Miller, Zachary A.; Mead, Christie; Watson, Christa; Welch, Ariane E; Henry, Maya L; Bourakova, Viktoriya; La Joie, Renaud; Bajorek, Lynn P.; Grinberg, Lea; et al.
ABSTRACT: A 66-year-old woman presented with agrammatism and apraxia of speech, meeting criteria for non-fluent/agrammatic variant primary progressive aphasia (nfvPPA). However, three years later, she developed frontal/executive, short-term phonological memory, visuospatial, and visual memory deficits suggesting involvement of multiple brain networks. Multimodal neuroimaging showed damage of both fronto-striatal and posterior brain regions. She was found to have multiple pathological processes: corticobasal degeneration (CBD), Alzheimer's disease (AD), and TAR DNA-binding protein (TDP)-43 type A. We hypothesize that cognitive and neuroimaging findings consistent with damage to multiple brain networks, each associated with vulnerability to certain molecular disease subtypes, could indicate mixed pathology.